Telephone Consultation and Prescription in Pediatrics: Contributing Factors and Impact on Clinical Outcomes - Haddad, Raymond N.; Sakr, Celine; Khabbaz, Lydia; Azouri, Hayat; Eid, Bassam (Frontiers in Pediatrics, 2020)
Objectives: To evaluate phone-based consultation practices and drug prescription profiles in pediatrics and to highlight their possible uses, contributing factors, and effects on clinical outcomes. Background: The ownership and everyday use of cell phones are increasing worldwide. Telehealth is gaining the support of health professionals for the delivery of simple healthcare measures to more complex management decisions. Despite this, in our country, doctors have been advised by concerned authorities to avoid any phone-based medical activity as the safety of such practices is still not well-established, especially among vulnerable pediatric patients. Patients and Methods: This cross-sectional study was conducted on a national level over 5 months. Phone consultations and prescription behaviors data were collected through a self-administrated questionnaire. The target population consisted of pediatric-trained physicians with at least 1 year of experience. Factors influencing telephone prescriptions were assessed using bivariate analysis. Results: Of among 120 included physicians (75.0% male), 64.2% were general pediatricians, 77.5% practiced in private clinics, and 27.5% had more than 20 years of work experience. All participants gave medical advice over the phone; 61.7% considered that they should be reimbursed for these activities and 29.2% of them reviewed 50% of their patients for the same complaint. A total of 109 participants (90.8%) prescribed drugs using a direct phone call (80.7%), SMS (27.5%), or WhatsApp application (61.5%). Antipyretics (97.2%) and cough suppressants (48.1%) were the most frequently prescribed drugs. Pharmacists' corrective interventions were seen in 40.4% of prescriptions. Fever was the only symptom that was statistically associated with phone prescriptions. Prescribers seemed to be less experienced and were more likely to consider phone-based practices as reimbursable activities. Conclusions: Consultations and prescriptions through mobile phones are extremely frequent in pediatric practices, even when restricted by responsible authorities. Our results highlight the frequency of medical prescription errors and the need for corrective interventions by pharmacists. The current practice of telemedicine may not ensure the patient's safety but exists rather as a convenience. There is a need for proper oversight with a regulatory framework and input from all stakeholders, including pediatricians and pharmacists.